From a bipartite Gondwanan shelf to an arcuate Variscan belt: The early Paleozoic evolution of northern Peri-Gondwana - Stephan, Tobias; Kroner, Uwe; Romer, Rolf L.; Roesel, Delia (Earth-Science Reviews, 2019)
The Late Paleozoic Variscan Orogen of Europe and North Africa comprises reworked Neoproterozoic to Early Paleozoic crust of the northern Gondwanan shelf that collided with Laurussia. The orogen is characterized by an arcuate trend of the Rheic suture along two orthogonal orogenic arcs and an apparently arbitrary juxtaposition of contrasting paleogeographic proxies to the south of the suture. The comparison of the sedimentary provenance, paleontological, lithostratigraphic, tectonic, and magmatic record demonstrates a contiguous but bipartite, i.e. a western and an eastern, shelf to the south of the Rheic Ocean. Here we reconstruct the development and architecture of the Paleozoic shelf of northern Gondwana preceding the formation of Pangea. In the early Paleozoic both shelf segments were affected by a heterogeneous extension whereby age and composition of extension-related magmatic rocks varies systematically from Cambrian alkaline and tholeiitic rocks in the western shelf to Ordovician calc-alkaline and peraluminous rocks in the eastern shelf. The regional variation in age and composition of the magmatic rocks reflects an eastward decreasing rate of extension along northern Gondwana. The higher extension in the western shelf culminated in the formation of the Armorican Spur. The subsequent intra-Ordovician compressional event, i.e. the "Sardic phase" and the "Cenerian orogeny", exclusively affected the eastern shelf. Early Devonian collision of the Armorican Spur with Laurussia initiated the subduction accretion stage of the Variscan orogeny resulting in the formation of the Rheno-Hercynian-MoravoSilesian Arc. At that time, the eastern shelf remained in a passive margin setting. Triggered by Late Devonian rifting along the eastern margin of Arabia, the eastern shelf decoupled from the Gondwanan plate and was displaced eastward, parallel to the northern margin of remaining mainland Gondwana. Early Carboniferous collision of the eastern shelf with the western shelf resulted in orogen wide transpressional tectonics and the formation of the Ibero-Armorican Arc. The tectonic interplay between the two Gondwanan shelf segments is the underlying cause of the final patchwork pattern of paleogeographic markers and the arcuate shape of the Variscan orogenic belt.
Keywords: Pangea; Variscan orogeny; Paleogeography; Detrital zircon provenance; Sardic phase; Ollo de Sapo